(3OQGSI JWHjbjI bjGSjI dfeGPL GdJfejI GdGbJUGOjIs - (3hdjO YHO GdMejO(B, (3YGjHs ((3HjQhJ(B:s (3ecJHI MSf GdYUQjI(B,s, 2010)
(3OhQ GdOhdI aj JMbjb GdGSJbQGQ GdGbJUGOj Gdcdj h GdGWGQ GdfXQj dg , GdSjGSI GdGbJUGOjI cCOGI dJMbjb GdGSJbQGQ GdGbJUGOj Gdcdj h ehbY SjGSI GdGfaGb GdMchej ef GdSjGSI GdGbJUGOjI , CKQ SjGSI GdGfaGb GdMchej Ydi (B: (3GdJhGRf GdGbJUGOj , GdJVNe h GdGSJbQGQ GdGbJUGOj GdNGQLj , eQGMd JWhQ GdSjGSI GdGbJUGOjI aj GdGbJUGO GdLRGFQj (B: (3NdGd eQMdI GdGbJUGO GdeNWW , GNJdGd GdGSJbQGQ GdGbJUGOj Gdcdj h HQfGeL GdGUdGMGJ GdGbJUGOjI , GfYcGS GdSjGSI GdGbJUGOjI Ydi GdGSJbQGQ GdGbJUGOj NdGd GdaJQI (B1990 (3`` (B2007 (3h JWhQ GdGfaGb GdMchej NdGd gPg GdaJQI aj GdLRGFQ , JMdjd CKQ SjGSI GdGfaGb GdMchej Ydi echfGJ GdYQV h GdWdH h Ydi eLedGJ GdWdH Gdcdj h Ydi GdeSJhi GdYGe ddCSYGQ h GdJhGRf GdNGQLj(B.s
(3eQGLY U(B.392 (3; edGMb U(B.372 (3bGFeI GdGTcGd U(B.21(3; bGFeI GdLOGhd U(B.25s
Keywords: (3GdGbJUGOs; (3GdGbJUGO Gdcdjs; (3GdJfejI GdEbJUGOjIs; (3GdfabGJ GdMchejIs